Frequency distribution of hypocalcification on permanent teeth in people with down syndrome at POTADS bandung foundation: A cross-sectional study - Budiman, Amelia Ambarwati; Andisetyanto, Prima; Soewondo, Willyanti (Padjadjaran Journal of Dental Researchers and Students, 2024)
Introduction: Down Syndrome (Trisomy 21) is a genetic disorder, namely the presence of an extra chromosome on chromosome 21. Abnormalities in people with Down Syndrome can influence various factors and have distinctive physical characteristics, one of which is dental anomalies, including abnormalities in the structure of tooth enamel, enamel hypocalcification. The aim of this study was to determine the frequency distribution of hypocalcification of permanent teeth in people with Down Syndrome. Methods: This research uses descriptive methods with cross-sectional survey techniques. Subjects were obtained using the accidental sampling method, resulting in 30 children with Down Syndrome from POTADS Foundation, consisting of 13 boys and 17 girls. All children had been diagnosed with Down Syndrome by a pediatrician. Enamel hypocalcification is an abnormality in the structure of the enamel, characterized by the presence of opaque to whitish and brownish spots. Examination of enamel hypocalcification can be done through clinical examination with sufficient lighting. Data analysis used frequency dstribution. Results: The frequency of enamel hypocalcification on permanent teeth of people with Down Syndrome was 33.33%; consisting of 26.67% in central incisors, 3.33% in first molars, and 3.33% in central incisors and first molars. Distribution by gender showed 13.33% in boys and 20% in girls, based on age 3.33% at 7 years, 6.67% at 11 years, 3.33% at 12 years, 3.33% at 13 years, 3.33% at 14 years, 6.67% at 17 years, 3.33% at 21 years, and 3.33% at 22 years. Conclusions: The frequency distribution of enamel hypocalcification in the permanent teeth of individuals with Down Syndrome in Bandung was 33.33%. Hypocalcification was most common in central incisors and more prevalent in women.Distribusi frekuensi hipokalsifikasi gigi tetap pada penyandang sindrom down: studi cross-sectionalABSTRAKPendahuluan: Sindrom Down (Trisomi 21) merupakan kelainan genetik yaitu adanya kromosom ekstra pada kromosom 21. Kelainan pada penyandang Sindrom Down dapat memengaruhi berbagai faktor dan memiliki ciri fisik yang khas, salah satunya adalah anomali gigi, termasuk kelainan struktur email gigi yaitu hipokalsifikasi email. Tujuan penelitian ini adalah untuk mengetahui distribusi frekuensi hipokalsifikasi gigi tetap pada penyandang Sindrom Down. Metode: Penelitian ini menggunakan metode deskriptif dengan teknik survei cross-sectional. Subjek yang diperoleh dengan metode accidental sampling menghasilkan sebanyak 30 anak penyandang Sindrom Down dari Yayasan POTADS, terdiri dari 13 laki-laki dan 17 perempuan. Anak penyandang Sindrom Down adalah anak yang telah didiagnosis mengalami Sindrom Down oleh dokter anak. Hipokalsifikasi email merupakan kelainan struktur email yaitu adanya bercak tidak tembus cahaya, buram sampai berwarna keputihan, dan berwarna kecoklatan. Pemeriksaan hipokalsifikasi email dapat dilakukan melalui pemeriksaan klinis dengan pencahayaan yang cukup. Analisis data menggunakan distribusi frekuensi. Hasil: Frekuensi hipokalsifikasi email pada gigi tetap penyandang Sindrom Down sebesar 33,33%; terdiri dari 26,67% pada gigi insisivus sentral, 3,33% pada gigi molar pertama, dan 3,33% pada gigi insisivus sentral dan molar pertama. Berdasarkan jenis kelamin 13,33% pada laki-laki dan 20% pada perempuan, berdasarkan usia 3,33% pada 7 tahun, 6,67% pada 11 tahun, 3,33% pada 12 tahun, 3,33% pada 13 tahun, 3,33% pada 14 tahun, 6,67% pada 17 tahun, 3,33% pada 21 tahun, dan 3,33% pada 22 tahun. Simpulan: Distribusi frekuensi hipokalsifikasi email pada gigi tetap penyandang Sindrom Down sebesar 33,33%, Hipokalsifikasi paling banyak terjadi pada gigi insisivus sentral dan lebih banyak terjadi pada penderita berjenis kelamin perempuan.